Review of Givira Walker, 1856 (Lepidoptera: Cossidae: Hypoptinae) with description of a new species - Naydenov, Artem E.; Yakovlev, Roman V.; Penco, Fernando C. (Zootaxa, 2024)
American carpenter moths from the genus Givira Walker, 1856 are reviewed to expand knowledge on the subfamily Hypoptinae Neumoegen & Dyar, 1894. Features of the genus and three previously known species are redescribed and detailed diagnoses are provided for each taxon. The fourth species of the genus—Givira cinnamonea sp. nov. from Brazil (Minas Gerais)—is described. Up-to-date distributional maps are provided.